EFFECTIVENESS OF SELF INSTRUCTIONAL MODULE ON KNOWLEDGE AND PRACTICE REGARDING BIOMEDICAL WASTE MANAGEMENT AMONG LAB TECHNICIANS OF SELECTED LABORATORIES IN CHENNAI CITY - DR.P.MANGALA GOWRI (International Journal of Pharma and Bio Sciences, 2014)
Introduction: Biomedical waste is any unwanted residual matter arising from the hospital and other health care settings. Biomedical waste management means a systematic way of disposing the health care waste. Lab Technicians involve in segregation, storage, transportation and disposal. Objective: To assess the knowledge and practice of biomedical waste management and to determine the effectiveness of self instructional module among lab technicians. Methods: Quasi experimental research design was obtained with 50 samples by lottery method from selected laboratories in Chennai. Pretest knowledge and practice was assessed by using structured questionnaire and checklist and self instructional module was administered. On 7th day post test was done by same structured questionnaire and checklist. Results: There was a significant increase in the knowledge and practice at the level of P<0.001 Conclusion: The medical laboratory is equipped with the needle dispenser as well as lab technicians are following the color coded bags to dispose waste.